Factors determinants the choice of mobile service providers: structural equation modeling approach on Bangladeshi consumers - Haque, A. K. M. Ahasanul; Rahman, Sabbir; Rahman, Mahbubur (Faculty of Economics and Administrative Sciences, Bursa, Turkey, 2010)
The aim of this study is to find out what were the factors that may have played significant role to select the telecommunication service providers. In general this research has an intention to develop a research framework grounded on a strong theoretical and literature review background. The survey instruments employed on Bangladeshi consumers included demographic background, price, service quality, product quality and availability and promotional offers for consumer perception. Thus the structural equation modeling approach was necessary in order to examine the variables. The data analysis was conducted using SPSS and AMOS (Analysis of Moment Structure) with the software package for windows. From the result it is revealed that paths are related to the casual processes significantly. Among all the significant variables, from our result, Price is the most important among our respondents followed by Service quality, product quality and promotion. Further research should be considered to gather more information regarding the service quality and customers’ satisfaction dimensions in context of the Bangladeshi mobile phone operators. It is hoped that the findings of this study may assist mobile phone industry in Bangladesh about their services and promotion of their services. However, the findings of this study may provide needed feedback and contribute to the improvement of players’ strategy and their marketing program.